Building Teacher Engagement through Value Fit and Organizational Support: The Mediating Role of Commitment - Martins, Simião de Andrade; Lianto, Lianto; Ginting, Sunardi (Economics and Digital Business Review, 2026)
Employee engagement is a critical determinant of organizational effectiveness in the education sector, particularly in developing countries where institutional systems are still evolving. This study examines the effects of Person-Organization Fit (P-O Fit) and Perceived Organizational Support (POS) on Employee Engagement (EE), with Organizational Commitment (OC) as a mediating variable. A quantitative explanatory design was employed involving 163 teachers from Catholic private secondary schools in Dili, Timor-Leste. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0. The results indicate that P–O Fit and POS have positive and significant effects on Organizational Commitment and Employee Engagement. Organizational Commitment also significantly influences Employee Engagement. Mediation analysis reveals partial mediation, with OC mediating the relationship between POS and EE and marginally mediating the relationship between P-O Fit and EE. The model explains 48.9% of the variance in employee engagement. These findings highlight the central role of organizational commitment in transforming value alignment and institutional support into stronger teacher engagement. The study contributes to engagement literature within faith-based educational institutions in developing country contexts